Training of Trainers for Women Anti-Drug Dealers in Bagan Deli Village - Sunarmi; Suhaidi (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
This cadre is focused on housewives in Bagan Deli Village. This regeneration process will certainly give birth to cadres of housewives who are anti against drug dealers. The material in this cadre is about the importance of cadre housewives in the Bagan Deli Village so that they can avoid the effects caused as drug dealers. From this dedication activity, it can be concluded that: In Bagan Deli Village, no woman has been arrested for drug trafficking; Women in Kelurahan Bagan Deli know that many around them have become drug addicts and dealers but are still afraid to report it; and Women in Bagan Deli Sub-district have started to get information on where to report if they see, hear and know about drug addicts and distribution.